Perception on environmental concern of pesticide use in relation to Framers’ knowledge (Journal of Environmental Science and Natural Resources, 2022)
Chemical pesticides are indiscriminately used for pest management and vector control. However, many farming communities are unaware of the dangers associated with the chemicals. This study assessed vegetable farmers' perception of the environmental impact of pesticide use in Bangladesh concerning the farmers’ knowledge and type. The farmers' socioeconomic characteristics and their relationship to some of the study variables, their attitude towards pesticides' environmental consequences, and their level of pesticide related knowledge were investigated. In this study, 882 farmers from nine districts participated through in-depth interviews and observations on-farm. The majority of farmers were males aged between 30 and 40 (32.44% in winter and 32.87% in summer). Moreover, 29.77% of the winter vegetable growers can sign their name only, but for the summer season’s 31.02% were educated up to high school. For the winter season, the highest 74.44% of respondents belonged to focal farmers who believed pesticides could be hazardous to their health. Only 1.68% of control farmers agreed pesticide use could lead to secondary pest resurgence. For the summer season, farmers were most concerned (60.19%) about the health risks to farm-workers, while secondary pest resurgence was the least concerned. In general, the focal farmers had a high level of knowledge and concern about pesticide hazards compared to the proximal and control farmers. Comprehensive intervention measures are required to mitigate pesticide-related health and environmental risks, including pesticide safety training programs for farmers, which could promote sustainable agricultural development while minimizing the environmental and health risks of pesticide misuse.Environ. Sci. & Natural Resources, 13(1&2): 94-99, 2020